The Emerald international handbook of feminist perspectives on women's acts of violence - Banwell, Stacy; Black, Lynsey; Cecil, Dawn K.; Djamba, Yanyi K. (Yanyi Kasongo), 1960-; Kimuna, Sitawa R.; Milne, Emma (Law professor) (Emerald handbooks., 2023)
"[This book] highlights and challenges normative accounts of women's violence and offers new multidimensional conceptualisations of these acts, furthering understanding of this topic from a feminist perspective ... Contributors present a comprehensive introduction to a wide range of international and interdisciplinary scholarship on different aspects of women's violence. Drawing on both empirical and secondary data, chapters incorporate familiar themes of intimate violence, homicide, terrorism and combat as well as wider content such as women's involvement in violent nationalist movements and their role in perpetrating obstetric harms"--Publisher's description.